2021
DOI: 10.1177/10711007211003090
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Different Methods of Measuring Pronation of the First Metatarsal on Weightbearing CT Scans

Abstract: Background: There is no consensus in the foot and ankle literature regarding how to measure pronation of the first metatarsal in patients with hallux valgus. The primary purpose of this study was to compare 2 previously published methods for measuring pronation of the first metatarsal and a novel 3-dimensional measurement of pronation to determine if different measurements of pronation are associated with each other. Methods: Thirty patients who underwent a modified Lapidus procedure for their hallux valgus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Furthermore, their cohort of 30 patients was significantly smaller than ours. 8 Although many other hindfoot/forefoot interactions, including compensatory changes, have been well described previously, 6,17,24,27 this is the first study, to our knowledge, to report a correlation between hindfoot alignment and M1 axial rotation using true WBCT. Compensatory forefoot supination/varus has been demonstrated in the setting of a planovalgus deformity and often is partially corrected with an opening wedge medial cuneiform osteotomy (Cotton osteotomy).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, their cohort of 30 patients was significantly smaller than ours. 8 Although many other hindfoot/forefoot interactions, including compensatory changes, have been well described previously, 6,17,24,27 this is the first study, to our knowledge, to report a correlation between hindfoot alignment and M1 axial rotation using true WBCT. Compensatory forefoot supination/varus has been demonstrated in the setting of a planovalgus deformity and often is partially corrected with an opening wedge medial cuneiform osteotomy (Cotton osteotomy).…”
Section: Discussionmentioning
confidence: 66%
“…They also demonstrated the importance of using a consistent method of measuring M1 axial rotation, as different reference points can yield significantly different results. 8 M1 rotation, in either direction, may also be associated with hindfoot varus and valgus deformity and could influence operative management and outcomes. For example, a patient with a pes planovalgus deformity may also have a symptomatic bunion with M1 malrotation that may possibly benefit from a derotational procedure in addition to a flatfoot reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Five months was chosen as the minimum follow-up for postoperative WBCT scans because patients are expected to be fully weightbearing at this time and has been used as the minimum follow-up in other WBCT scan studies that have demonstrated postoperative changes in first metatarsal pronation. 12 Postoperative WBCT scans were used in this population to assess healing of the arthrodesis site. Patients were also excluded from the study if their primary TMT fusion during the time period was a revision surgery for a HV deformity, if the modified Lapidus procedure was performed as part of another procedure such as a reconstruction of a progressive collapsing foot deformity, or in the setting of midfoot arthritis or concomitant hindfoot pathology.…”
Section: Methodsmentioning
confidence: 99%
“…The advent of weightbearing CT (WBCT) scans has built off earlier work using weightbearing radiographs by Saltzman et al and others 20,49 and allowed examiners to quantify the 3-dimensional HV deformity, especially the first metatarsal pronation deformity. 3,6,8,12,18,28,29,41,46 Although there is no commonly accepted method to measure first metatarsal pronation, previous studies have demonstrated a mean increase in first metatarsal pronation between 2 and 13 degrees in patients with HV compared with normal control patients. 3,6,12,18,28,29,41,46 However, other recent studies have demonstrated a wide range of first metatarsal pronation in patients without HV, which has called into question the clinical importance of the first metatarsal pronation deformity in HV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation